Hypnotherapy Can Reduce Anxiety Score In High Risk Pregnant Women - Anida Izatul Islami; Triana Sri Hardjanti (Jurnal Kebidanan dan Kesehatan Tradisional, 2022)
Background: A high-risk pregnancy can affect the psychological, social, and emotional conditions, feel afraid and anxiety. Excessive anxiety can trigger uterine contractions, abortion, and hypertension that can trigger the occurrence of preeclampsia. Hypnotherapy is one of the relaxation techniques that are done by opening the subconscious so that all forms of positive affirmations given by the therapist can be absorbed properly. Techniques like this can become good habits by empowering pregnant women so that they can get used to making positive affirmations. Methods: This study uses quasy experimetal deisgn, respondents in the study were pregnant women who were at high risk based on the Poedji Rochyati scorecard and experienced anxiety based on the HARS questionnaire in July-August 2021. This intervention was given three sessions in 1 week for 40-50 minutes. This research process has been through informed consent from respondents. Results: After three sessions of hypnotherapy each sample showed an effect. This can be seen from the total number of anxiety scores after the final therapy session is given. At the end of the session, two pregnant women experienced a category decrease to mild anxiety, namely Mrs N and Mrs Q. The other three pregnant women did not experience a category decrease but experienced a decrease in anxiety scores. However, all pregnant women in the study sample experienced a decrease in anxiety scores. Conclusion: Hypnotherapy can be concluded that hypnotherapy can help pregnant women at high risk of reducing anxiety during the Covid-19 pandemic